2019
DOI: 10.21203/rs.2.10988/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR825 and miR825* function as negative regulators in Bacillus cereus AR156-elicited systemic resistance to Botrytis cinerea in Arabidopsis thaliana

Abstract: Background: Small RNAs function to regulate plant defense responses to pathogens. We previously showed that miR825 and miR825* downregulate Bacillus cereus AR156 (AR156)-triggered systemic resistance to Pseudomonas syringae pv. tomato DC3000 in Arabidopsis thaliana (Arabidopsis). The aim of this study was to unravel the role of miR825 and miR825* in AR156-mediated systemic resistance to Botrytis cinerea B1301 in Arabidopsis. Results: Northern blotting revealed that miR825 and miR825* were more strongly downreg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…Liu et al found that BR signal transduction pathway-related genes were upregulated after infection with Botrytis c. , and exogenous BR enhanced its defence response to Botrytis c. , indicating that BR was involved in the resistance of rose to Botrytis c [ 12 ].. Exogenous 2,4-Epibrassinolide improves the resistance of grapes to Botrytis c. by inhibiting spore germination of Botrytis c. and enhancing the sensitization mechanism of grape fruit [ 13 , 14 ]. In addition, some microRNAs are also involved in plant defence against Botrytis c. Nie et al found that overexpressed miR825 and miR825 * improved the susceptibility of Arabidopsis to Botrytis c. In contrast, silencing miR825 and miR825 * enhanced the resistance of Arabidopsis to Botrytis c. , indicating that mir825 and mir825 * play a negative regulatory role in Arabidopsis defence against Botrytis c [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found that BR signal transduction pathway-related genes were upregulated after infection with Botrytis c. , and exogenous BR enhanced its defence response to Botrytis c. , indicating that BR was involved in the resistance of rose to Botrytis c [ 12 ].. Exogenous 2,4-Epibrassinolide improves the resistance of grapes to Botrytis c. by inhibiting spore germination of Botrytis c. and enhancing the sensitization mechanism of grape fruit [ 13 , 14 ]. In addition, some microRNAs are also involved in plant defence against Botrytis c. Nie et al found that overexpressed miR825 and miR825 * improved the susceptibility of Arabidopsis to Botrytis c. In contrast, silencing miR825 and miR825 * enhanced the resistance of Arabidopsis to Botrytis c. , indicating that mir825 and mir825 * play a negative regulatory role in Arabidopsis defence against Botrytis c [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include genes that impact resistance against biotrophic pathogens such as accelerated cell death 6 ( ACD6 ) and Cysteine-rich receptor-like kinase CRK13 [ 71 ] that positively regulate SA signalling [ 72 ], as well as Calmodulin-like CML41 that regulates flg22-induced stomatal closure [ 73 ]. Furthermore, miR825 target AT3G04220 [ 74 ] and the lipid transfer protein AZI3 [ 75 ] contribute to defence against necrotrophs and the lectin receptor kinase LecRK4.1 positively regulates Arabidopsis PTI and resistance against biotrophic and necrotrophic pathogens [ 76 ]. Reduction in expression of these genes is likely to contribute to the observed enhanced susceptibility of RxL21 over-expressing plants to both biotrophic and necrotrophic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…12 ). Interestingly, during preparation of this manuscript, a report established miR825-5p and 3p are involved in ISR triggered within the B. cereus / Botrytis cinerea pathosystem [76]. In regards to the transcriptional down regulation of MIR825 , a recent report showed that mutations that lead to over accumulation and nuclear localization of TNL protein SNC1 repress transcription of MIR genes, including MIR825 [54].…”
Section: Discussionmentioning
confidence: 99%